2008
DOI: 10.1152/ajpheart.00406.2007
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter air pollution exposure promotes recruitment of monocytes into atherosclerotic plaques

Abstract: demiologic studies have shown an association between exposure to ambient particulate air pollution Ͻ10 m in diameter (PM10) and increased cardiovascular morbidity and mortality. We previously showed that PM10 exposure causes progression of atherosclerosis in coronary arteries. We postulate that the recruitment of monocytes from the circulation into atherosclerotic lesions is a key step in this PM10-induced acceleration of atherosclerosis. The study objective was to quantify the recruitment of circulating monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 53 publications
5
63
0
Order By: Relevance
“…Work done by our laboratory at the James Hogg Research Center showed structural changes in atherosclerotic plaques from Watanabe Heritable Hyperlipidemic (WHHL) rabbits exposed to PM 10 (Suwa et al, 2002;Tranfield et al, 2010;Yatera et al, 2008) and from ApoE -/-mice exposed to diesel exhaust (Bai et al, 2011). The observed changes were consistent with atherosclerotic plaques vulnerable to rupture.…”
Section: Medical Research Investigating How Exposure To Particulate Msupporting
confidence: 56%
“…Work done by our laboratory at the James Hogg Research Center showed structural changes in atherosclerotic plaques from Watanabe Heritable Hyperlipidemic (WHHL) rabbits exposed to PM 10 (Suwa et al, 2002;Tranfield et al, 2010;Yatera et al, 2008) and from ApoE -/-mice exposed to diesel exhaust (Bai et al, 2011). The observed changes were consistent with atherosclerotic plaques vulnerable to rupture.…”
Section: Medical Research Investigating How Exposure To Particulate Msupporting
confidence: 56%
“…Rabbits were sacrificed at 42 and 46 weeks of age at the completion of a four-week exposure protocol. The rabbits used in the present study were also used in other investigations to address monocyte release from the bone marrow (20) and monocyte recruitment into atherosclerotic plaques (32).…”
Section: Methods Animalsmentioning
confidence: 99%
“…The model used to test the hypothesis of the present study has been established in the James Hogg iCAPTURE Research Centre, Providence Heart + Lung Institute (Vancouver, British Columbia), and is well characterized with regard to both the local and the systemic response (20,26,32,36,37). Briefly, the experimental rabbits (n=8) were lightly anesthetized with 5% halo thane while 5 mg of EHC-93, suspended in 1 mL of sterile saline, was deposited just above the larynx using a blunt curved needle twice per week for four weeks.…”
Section: Exposure Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PM exposure is able to significantly alter the function and responses of platelets both in vitro and in vivo including induction of Ca(2+) release, dense granule secretion and surface expression of platelet activation markers like P‐selectin expression, as well as aggregation, and change in the mean platelet volume 142, 143, 144, 145, 146. Particulate matter exposure/treatment has been shown to modify the function of monocytes significantly including inflammatory response and cytokine production, recruitment and mobilization, and transcriptional and translational modulations of gene expressions in monocytes 135, 136, 147, 148, 149, 150, 151, 152. Further studies are needed to determine the complex relations between PM exposure, monocyte and platelet function, and progenitor cells/SCs.…”
Section: Other Considerationsmentioning
confidence: 99%